Exploring Character Education Values in Dayak Kanayatn Folktales and Their Potential as Social Studies Learning Resources - Saiful Bahri; Haris Firmansyah; Emi Tipuk Lestari; Sandra Fitria Wardani (CV. Rayyan Dwi Bharata, 2026)
This study explores character education values embedded in Dayak Kanayatn folktales and analyzes their potential as Social Studies learning resources. This qualitative study employed content analysis of five folktales: Ria Sinir and Dara Itam, Pantak Kayu Mamo, Ne' Unte', Ne' Baruakng, and Desa Samuah Labur. The data were analyzed by identifying narrative units, coding values, constructing thematic categories, and mapping their relevance to Social Studies learning. The findings reveal five value domains: moral-personal, social-communal, spiritual, ecological, and civic-cultural values. Dayak Kanayatn folktales preserve local ways of understanding relationships with family, community, ancestors, nature, customary norms, and social responsibility. In Social Studies, these folktales can support critical reading, value discussion, social inquiry, cultural documentation projects, and reflective character learning.